Alasan Tiongkok Menjalin Kerja Sama Sektor Energi Migas Dengan Brunei Darussalam Tahun 2013-2018 - Putri Sanjiwani, Dewa Ayu; Kumala Dewi, Putu Ratih; Dharmiasih, D.A. Wiwik (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT This research aims to describe China Reasons to Establish Cooperation in Oil and Gas Energy Sector with Brunei Darussalam by using a qualitative method. China's claims in the South China Sea with the nine dash line triggered disputes with ASEAN countries including Brunei Darussalam. The cooperation between China and Brunei Darussalam was also established amid the condition of Brunei Darussalam's oil and gas energy resources which only lasted for about two decades. Therefore, Researcher uses two main concepts, which are bilateral cooperation and alliance in order to answer the motive behind China cooperation with Brunei Darussalam in 2013-2018. This research perceives that China had the desire to establish bilateral cooperation in an effort to seek an alliance from Brunei Darussalam in order to gain support in resolving the South China Sea dispute. Keywords: China, Brunei Darussalam, Bilateral Cooperation, Alliance